Unraveling the nomenclatural puzzle of the collared and white-lipped peccaries (Mammalia, Cetartiodactyla, Tayassuidae) - Acosta, Luis E.; Garbino, Guilherme S. T.; Gasparini, Germán M.; Dutra, Rodrigo Parisi (Zootaxa, 2020)
The nomenclatural history of the collared and white-lipped peccaries, two well-recognized taxonomic entities, has been confusing. From the 18th century to the beginning of the 20th century, several genera were created, most of them without an explicit designation of type species. Due to differing opinions as to whether the two species should be included in a single genus or, if separate genera were recognized, which generic name should be applied to each of the two taxa, the validity of generic and specific names oscillated until even recently. This paper aims to solve these nomenclatural issues by reviewing the different taxonomic arrangements of these two peccaries and applying appropriately the International Code on Zoological Nomenclature. We contend that the valid generic name for the white-lipped peccary is Tayassu Fischer, 1814 (type Sus pecari Link, 1795), while Dicotyles Cuvier, 1816 (type Dicotyles torquatus Cuvier, 1816) is the valid genus for the collared peccary, with Pecari Reichenbach, 1835 as its junior synonym.